Communication in Focus: Supervisors’ Lived Experiences - Gabriel Samala Jr (RSF Press, 2023)
As communication conflicts were happening in every organization, the goal of this study was to know the lived experiences of department supervisors regarding organizational communication principles and conflicts and to determine the best strategies to resolve these conflicts. A qualitative research design with the phenomenology approach was used in the study. There were ten department supervisors from the selected companies in Laguna, particularly in Biñan, Cabuyao, Calamba, and Sta. Rosa. The participants were interviewed in a semi-structured manner. The result showed department supervisors' different perspectives and practices regarding organizational communication principles and conflicts. Using the Hermeneutical Phenomenological Method, the study generated ten emerging themes which were: Maintaining Goals and Objectives, Various Experiences in Communication, Language Barriers, Interpersonal Communication, Relationship, Poor Communication and Differences, Cultural, Personal, and Organizational Barriers, Diverse Effects of Conflicts, Clear Understanding and Communication, Proper Communication, and Development in Work Performance and Organization. Communication plays a vital role in an organization achieving its goal and objectives. The barriers that contributed to organizational communication conflicts served as a major challenge for the supervisor-participants. They utilized several strategies to cope with the challenges encountered. The supervisor-participants mentioned the development in the communication cycle in their organization. Finally, they practised the organizational communication principles in encountering conflicts with their managers, subordinates, and other organization members. The output of the study was proposed for them to be knowledgeable about the importance, barriers, challenges, and strategies of organizational communication principles and conflicts.